The Oxford handbook of sound and image in digital media - Vernallis, Carol; Herzog, Amy.; Richardson, John, 1964- (New York : Oxford University Press, 2013)
This text surveys the contemporary landscape of audiovisual media. This book volume look not only to changes brought by digital innovations, but to the complex social and technological past that informs, and is transformed by, new media. This collection is conceived as a series of dialogues and inquiries by leading scholars from both image- and sound-based disciplines. Chapters explore the history and the future of moving-image media across a range of formats including blockbuster films, video games, music videos, social media, digital visualization technologies, experimental film, documentaries, video art, pornography, immersive theater, and electronic music. Sound, music, and noise emerge within these studies as integral forces within shifting networks of representation. The essays in this collection span a range of disciplinary approaches (film studies, musicology, philosophy, cultural studies, the digital humanities) and subjects of study (Iranian documentaries, the Twilight franchise, military combat footage, and Lady Gaga videos). Thematic sections and direct exchanges between authors facilitate further engagement with the debates invoked by the text.
Cinema in the realm of the digital : foundational approaches -- Dialogue : screens and spaces -- Glitches, noise, and interruption : materiality and digital media -- Uncanny spaces and acousmatic voices -- Dialogue : visualization and sonification -- Virtual worlds, paranoid structures, and states of war -- Blockbusters : franchises, remakes, and intertextual practices -- Dialogue : de-coding source code -- Rethinking audiovisual embodiment -- Sounds and images of the new digital documentary -- Modes of composition : digital convergence and sound production -- Digital aesthetics across platform and genre.
Includes bibliographical references and index.
Keywords: Sound in mass media; Digital media -- Technological innovations; Sound -- Social aspects